Reaching for the Techno-Nationalist Toolbox: What are the breeding grounds for state-directed internet shutdowns? - Sanchez, Conor L. (Tufts Archival Research Center, 2019)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Governments around the world, particularly in developing countries, are exhibiting an increased willingness to hijack the internet’s control valves during bouts of social unrest. Since 2011, the number of instances and the frequency with which nation-states have disconnected internet or mobile networks has increased multifold. Whereas previous work on this subject has focused on how physical vulnerabilities, such as a dearth of international internet connections, make countries more at risk of experiencing shutdowns, this paper seeks to show how political, sociological, and institutional vulnerabilities are just as significant. It also goes beyond evaluating the potential economic costs of disruption, by identifying causal pathways that make countries more susceptible to shutdowns and thus, providing clearer visibility into what specific changes might deter governments from severing internet access. Using India as a case study, I identify a generally applicable set of ground conditions that lead to shutdowns. At a broader level, my conclusion states that a similar set of vulnerabilities in another country would raise the likelihood of governments acting on their more flawed inclinations when it comes to internet policy. This could come in the form of internet shutdowns but could also manifest in a number of different actions that fit within what I call the “techno-nationalist toolbox.” This research will be useful to all researchers, policymakers, and industry leaders interested in the intersection of the internet, policy, and development.